2019
DOI: 10.1007/s00285-019-01391-y
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between individual-based and continuum models of growing cell populations

Abstract: Continuum models for the spatial dynamics of growing cell populations have been widely used to investigate the mechanisms underpinning tissue development and tumour invasion. These models consist of nonlinear partial differential equations that describe the evolution of cellular densities in response to pressure gradients generated by population growth. Little prior work has explored the relation between such continuum models and related single-cell-based models. We present here a simple stochastic individual-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 66 publications
1
37
0
Order By: Relevance
“…Our analyses extend this framework to include apparent kinetics emergent from spatial and temporal variation in enzyme and substrate concentrations, which should be broadly applicable for scaling up microbial processes to the ecosystem scale. This emergence of a coarse-scale pattern from localscale kinetics is analogous to results from a cell population study by Chaplain et al (2018), who found that an individual-based model can generate complex spatial patterns of population growth observed in a corresponding continuum model.…”
Section: Eca Captures Kinetics Emergent From Spatial and Temporal Varsupporting
confidence: 76%
“…Our analyses extend this framework to include apparent kinetics emergent from spatial and temporal variation in enzyme and substrate concentrations, which should be broadly applicable for scaling up microbial processes to the ecosystem scale. This emergence of a coarse-scale pattern from localscale kinetics is analogous to results from a cell population study by Chaplain et al (2018), who found that an individual-based model can generate complex spatial patterns of population growth observed in a corresponding continuum model.…”
Section: Eca Captures Kinetics Emergent From Spatial and Temporal Varsupporting
confidence: 76%
“…Having rewritten the problem in this form allows us to construct travelling-wave solutions using an approach that builds on the method of proof recently presented in [12,31]. For the sake of brevity, in this section we drop the tildes from all the quantities in problem (4.6).…”
Section: Travelling-wave Solutions Of the Free-boundary Problemmentioning
confidence: 99%
“…These models are formulated in terms of nonlinear partial differential equations for cell densities (or cell volume fractions) and, as such, are amenable to both numerical and analytical approaches that enable insight to be gained into the biological system under study. From a mathematical perspective, over the past few years particular attention has been paid to the existence of travelling-wave solutions with composite shapes [5,12,31,43,48] and to the convergence to free-boundary problems in the asymptotic limit whereby cells are represented as an incompressible fluid [7,30,33,41,42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial structure in biological populations includes both clustering and segregation [32][33][34][35][36][37]. Stochastic individual-based models (IBM) offer a straightforward means of exploring population dynamics without invoking a meanfield approximation [38,39]. However, IBM approaches are computationally prohibitive for large populations and provide limited mathematical insight into the population dynamics, for example how particular biological mechanisms affect the carrying capacity or the Allee threshold [40].…”
Section: Introductionmentioning
confidence: 99%